Strategi Kepala Madrasah dalam Meningkatkan Kinerja Guru di Madrasah Aliyah Al Mujahidin Ciptodadi Sukakarya Kabupaten Musi Rawas Sumatera Selatan - Wahyudi, Wahyudi (STAI Denpasar Bali, 2024)
A headmaster in the organization is needed to bring the organization to its intended purpose. Improved performance of teachers is crucial regarding the success of the institution of school / madrasah, because of changes in the field of teacher education will be achieved. In this study, researchers sought to present the existence of a central figure, namely: the principal, who is considered to have contributed to the improvement of the performance of teachers in Madrasah Aliyah Al Mujahidin. This study used a qualitative approach with case study design. Data was collected through interview techniques, observation, and documentation. While data analysis techniques, researchers used data reduction, data presentation and verification. To check the validity of the data is done with credibility, transferability, dependability, confirmability, using a variety of sources, theories and methods in order to obtain objective data. The informants are: headmaster, waka curriculum, and 3 educators. The results showed that: (1) The role of headmaster in improving the performance of teachers in Madrasah Aliyah Al Mujahidin Ciptodadi are: a) the head of the madrasah as a supervisor, b) As an evaluator, c) As an educator. (2) Strategy headmaster in improving the performance of teachers in Madrasah Aliyah Al Mujahidin Ciptodadi Overlapping are: a) Generating the spirit of the performance of teachers by growing sense of belonging to the institution, b) Cooperation with other agencies to include workshops and training, c) Increase that task teachers, d) Form of intrinsic and extrinsic motivation is, e) to communicate persuasively and provide welfare beyond basic salary, g) strategy gave the order in accordance with the duties and strategies reprimand, h) strategy receive suggestions and strategies for creating a disciplined group. (3) Impact headmaster strategy in improving the performance of teachers in Madrasah Aliyah Al Mujahidin Ciptodadi Overlapping are: a) Always make lesson planning, b) Using a variety of learning methods, c) Creating a classroom climate conducive, d) uses the medium of learning.